O trabalho social em política pública de habitação. Uma avaliação do caso de Viçosa do Ceará-CE - Brasil, Tricia Maria Marques do (2020)
After all, is technical social assistance indispensable when it comes to housing policies of social interest? This article search answers for this question through an analysis of the role and scope of Technical Social Work Project or in Portuguese Projeto de Trabalho Técnico Social (PTTS), under the Minha Casa Minha Vida Rural Program (PMCMV Rural). It is known that the agrarian issue in Brazil is not just a land problem, but that takes into account the fact that the rural workers are virtually invisible to the state and this neglect translates into social indicators that prove intolerable levels of poverty increased by the high housing insalubrity. The PMCMV Rural was created for the purpose of enabling the rural communities access to decent housing in the countryside, be it building a new home or renovating an existing one. In the current normative scope, every PMCMV Rural instance has to elaborate a PTTS, which is considered an important component in so far as it guides the technical social work to the full attainment of this housing policy, through mobilization, organization and participation of beneficiaries. Considering the institutional framework summarized above, the research is structured in the case study of the locality of Macajetuba site, countryside of the city of Viçosa do Ceará – Brazil, in a time frame that covers the period from 2015 to 2018. The adopted methodology is based on the in-depth evaluation model, using the quantitative analysis with quantitative data support. The data collect was performed through bibliographic documentary research, field observation, interviews and questionnaires, with further analysis of the statements of people involved besides tabulation in spreadsheets, creation and interpretation of graphs for the quantitative data. The results point to the fragility in the execution process of the PTTS. Firstly, the absence of a diagnosis of the attributes of the territory and the social dynamics of the intervention coverage area was observed. It was found that the PTTS action was diluted due to discontinuity in resource release and consequent slow construction of houses, which caused the interruption of the presence of social assistance. It is a shame specially the lack of a fundamental contribution of the technical social project to reinforce the sense of belonging and ownership of a particular community and act as a tool for social transformation.